Comparing street children who use inhalant in terms of suicide attempt - Tarı, Itır; Ziyalar, Neylan (Journal of Dependence, 2005)
Objective: The aim of the study was to compare street children who abuse inhalants in terms of suicide attempts, street living situation, substance use properties and high risk sexual behaviour.Method: This study was conducted in Yeldegir-meni Child and Adolescent center in Istanbul between January 2003 and May 2003. The first group is composed of 14 male inhalant abuser street children aged between 10-18 (mean) who have risky sexual behaviour and suicide attempts in their life time. The second group is composed of 16 male inhalant abuser street children aged between 10-18 (mean) who have risky sexual behaviour in their life time but no suicide attempts. (N:30). In the present study we used “National Assessment Program on Drug Abuse in Turkey” Project “Drug Abuser Community Sample” questionnaire developed by the United Nations Office on Drugs and Crime (UNODC). In the above form, the questions related to the demographic information and economic status, substance use history and sexual experiences are used in this study. An additional 21 questions about suicidal ideation, suicide planning and suicide attempts are also utilised in the study.Results: In both groups, the youngest subject was 15 and oldest subject was 17 years old. All participants were substance inhalers. Physical self harm was self reported to be %71.4 (n=10) in the suicide attempt grup and %37.5 (n=6) in the non-suicide attempt group.
Keywords: Inhalant; street children; suicide attempts